2020
DOI: 10.3390/ijerph17228444
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes During COVID-19 Confinement in France: A Web-Based Study

Abstract: Background: A global pandemic due to COVID-19 emerged in November 2019 and hit France in early March 2020. It not only resulted in a loss of lives, but also in very strict confinement measures. The objective of this study was to understand what the determinants of the changes in participants’ behavior and mental state were during the confinement. Methods: An online survey was launched on 23 April 2020 and closed on 7 May 2020. The final sample included 1454 participants from 24 to 65 years old. Descriptive and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 27 publications
(22 reference statements)
10
72
0
Order By: Relevance
“…In our study, the frequency of alcohol drinkers who increased and that of those who decreased alcohol intake with lockdown was very similar, around 15%. Compared to other surveys, the frequency of increased alcohol consumption was much lower in our population than in adults in Germany (34.7%) (51), Australia (20.0% (52) to 30.8% (53)) or the USA (29%) (54), and more similar to that reported in other Spanish (14,22), French (45,55), and Italian surveys (56). In fact, in these studies, declining alcohol consumption during quarantine was more common than increasing it.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, the frequency of alcohol drinkers who increased and that of those who decreased alcohol intake with lockdown was very similar, around 15%. Compared to other surveys, the frequency of increased alcohol consumption was much lower in our population than in adults in Germany (34.7%) (51), Australia (20.0% (52) to 30.8% (53)) or the USA (29%) (54), and more similar to that reported in other Spanish (14,22), French (45,55), and Italian surveys (56). In fact, in these studies, declining alcohol consumption during quarantine was more common than increasing it.…”
Section: Discussionsupporting
confidence: 74%
“…Results for changes in diet quality are difficult to compare because of differences in diet assessment across studies, with some showing the proportion of those who increased or decreased the consumption of certain products (11,15,56,57), others asking participants to report their self-perceived changes in quality (55,58), and only a few studies providing validated diet quality scores (17,18,59). Even for the latter, comparisons are limited due to the use of different scales; for instance, in a Spanish study, confinement was associated with a mean increase of 0.8 points in the MEDAS score (17), in one French study it was associated with a mean reduction of 0.32 points in the simplified PNNS-GS2 index (18), while in another study it was associated with equivalent increases or decreases in the Alternative Healthy Eating Index (59).…”
Section: Discussionmentioning
confidence: 99%
“…In some situations staying at home encouraged many individuals to eat a fresh, home-made, balanced diet 32 , as evidenced by a reduction in the consumption of fast food 33 , fewer purchases of ready-made meals, and by the dominance of online/in-person grocery shopping as the major source of food and food purchases in some countries 16,34 . A study from China showed that families that did online shopping included a greater variety of foods in their diet than in normal circumstances 35 .…”
Section: Dietary Habitsmentioning
confidence: 99%
“…In France, the confinement started on 17 March 2020 and lasted for 8 weeks, until 11 May 2020. This period had negative effects on many health behaviors [ 9 ] and was especially marked by the deterioration of the quality of sleep in the general population. From the very beginning of the confinement, three-quarters of the people reported trouble sleeping, compared with about a half in the last general population survey conducted before the confinement [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%